Indonesia’s Global Workers : Juggling Opportunities and Risks - World Bank (World Bank, Jakarta, 2017)
International labor migration is an important sector of the Indonesian economy in its own right, requiring commensurate efforts to improve its professionalism as a sector and instill modernization across its various components to maximize its potential for the benefit of all stakeholders.This report aims to point towards the best policy mix for Indonesia’s various international migrant worker groups who face widely differing risks and gain diverse economic benefits from migration. Following introduction, Section 2 of the report looks at the major profiles of Indonesian migrant workers and their reasons for migrating. Section 3 focuses on the discussion about female domestic workers. Section 4 delves into the issue of undocumented migration, including the government’s efforts to encourage documented migration. Section 5 then looks as how best to sustain the benefits of migration, with particular reference to a third profile of migrant workers, namely those who work in the more developed countries of East Asia and who generally earn the highest wages. Finally, Section 6 rounds off the report with broad policy recommendations